"Warn the Duke": The Sarajevo Assassination in History, Memory, and Myth. Issue 1 (1st March 2019) - Miller-Melamed, Paul
Abstract : How has the Sarajevo assassination been conjured and construed, narrated and represented, in a wide variety of media including fiction, film, newspapers, children's literature, encyclopedias, textbooks, and academic writing itself? In what ways have these sources shaped our understanding of the so-called "first shots of the First World War"? By treating the assassination of Archduke Franz Ferdinand (28 June 1914) as a "site of memory" à la historian Pierre Nora, this article argues that both popular representations and historical narratives (including academic writing) of the political murder have contributed equally to the creation of what I identify here as the "Sarajevo myth."